Requirements for Police Officer’s Personality in Terms of Globalization and the Implementation of International Standards of Law Enforcement Officers’ Conduct - D. V. Shvets; N. O. Rastorguyeva (Bulletin of Kharkiv National University of Internal Affairs)
The emphasis has been placed on the fact that the training of law enforcement officers must currently take into account the global challenges to society, the state and the international community.